Family Firms as Institutions: Cultural reproduction and status maintenance among multi-centenary shinise in Kyoto. Issue 6 (June 2019) - Sasaki, Innan; Ravasi, Davide; Micelotta, Evelyn
Our study investigated how multi-centenary family firms in the area of Kyoto – collectively known as shinise – maintain a high social status in the community. Our analysis unpacks the socio-cultural practices through which the ongoing interaction among these actors re-enacts and reproduces the social order that ascribes shinise a distinct social standing in exchange for their continued commitment to practices and structures that help the community preserve its cultural integrity and collective identity. By doing so, our findings trace a connection between status maintenance and the expressive function that a category of firms performs within a community. At the same time, our study reveals a dark side of high status, by showing how their commitments lock shinise in a position of 'benign entrapment' that may impose sacrifices on family members and severe limitations to their personal freedom.